The Response of The Addition of Ginseng Leaves (Talinum Paniculatum Gaertn) Mix Supplements in Rations to The Performance of Broiler Production - Yurni Sari Amir; Ulva Mohtar Lutfi; Ramond Siregar; Nelzi Fati; Dihan Kurnia (UNIVERSITAS ISLAM LAMONGAN, 2021)
The aim of this study was to determine the response of adding ginseng leaf supplements (Talinum Paniculatum Gaertn) to the diet on the introduction of meat products, including dietary intake, body weight gain and dietary transformation in broilers. The subjects of the study were 100 broilers with five treatments and four replicates grown from DOC for 33 days. A control treatment was a 100% mixed diet (A), and B was a mixed died with 0.5% ginseng leaf mixture supplement. Treatment C was a mixed died with 1% ginseng leaf mixture supplement, with 1.5% ginseng leaf mixture supplement (D treatment), and with 2% additive to the ginseng leaf mixture (E treatment). The blended diet consisted of corn, palm meal, soybean meal, fishmeal, oil, and top mix. The variables measured were diet intake, weight gain, and diet conversion. The research method used an experiment with a completely randomized design. The results showed that the addition of the ginseng leaf meal feed additive to the diet had no significant effect (P> 0.05) on dietary intake, body weight gain, and diet conversion. The conclusion of this study is that the addition of up to 2% of the ginseng leaf meal feed additive to the diet did not negatively affect the appearance of the product and broilers.